Internet of things in manufacturing: A review. (2022) - Garg, Khushbu; Goswami, Chandramani; Chhatrawat, R.S.; Kumar Dhakar, Shyam; Kumar, Govind
Abstract: Internet of things (IoT) make a major contribution in the manufacturing industries by connecting the objects with the help of network and remotely controlled the existing network infrastructure, initiation of opportunities for integration of the manufacturing world to the computer-based systems, this results the enhanced production efficiency, product accuracy and economic growth in addition to minimum human intervention. In this review we have discussed about the modern technologies for the accomplishment of the smart manufacturing. The aim of this paper is to fulfill the objective of developing the discrete event-based system for Men, Materials and Plant & Equipment (MMP) on the manufacturing site, for that the primary focus on reviews the different ways to implement the Internet of Things (IoT) at the project site and improve the material handling, labor monitoring and tracking the plant and equipment for better productivity and efficiency of the overall project.